Moisture availability and agricultural potentialities of Mali and Niger - E. Ofori- Serpong (Indonesian Journal of Geography, 1990)
One of the greatest factors limiting agricultural development in arid and semi-arid regions of Africa is lack of moisture. A country with adequate moisture has a great potential for agricultural development. It is againts this background that this paper focuses on the application of Hargreaves monthly moisture availability index classification to Mali and Niger in West Africa. The two countries are classified into moisture regions on the basis of the index and their relative agricultural potentials are assessed.